Promising Directions in Chemical Processing of Methane from Coal Industry. Part 4. Long-term Stability Test - Е.V. Matus; O.V. Tailakov; O.B. Sukhova; A.V. Salnikov; O.A. Stonkus; M.A. Kerzhentsev; S.R. Khairulin; Z.R. Ismagilov (Eurasian Chemico-Technological Journal)
For the processing of coal mine methane into hydrogen-containing gas, a catalytic process of methane tri-reforming was studied under long-term testing conditions (800 ᵒC, 100 h). The tests were carried out using the actual composition of the methane-containing mixture recovered by mine drainage systems of the Raspadskaya mine (Kuzbass, Russia). Gas chromatographic analysis of coal mine gas showed that it contains the following components with an average concentration, vol.%: CH4 – 40.18, N2 – 36.30, H2O – 12.90, O2 – 9.77, CO2 – 0.88, C2H6 – 0.25 and C3H8 – 0.04. It was found that the average O/C molar ratio was 0.87, so CO2 addition to the methane-containing mixture was done to maintain the O/C ratio > 1.1 to ensure stable operation (without significant coke formation) during the catalytic process. Long-term catalytic tests have shown high parameters of the methane tri-reforming process, which were stable over the time of operation. At a temperature of 800 ᵒC, after 100 h of process using the Ce0.2Ni0.8O1.2/Al2O3 catalyst, the hydrogen yield was 85% at a methane conversion of 80%. A comparative analysis of the properties of fresh and spent Ce0.2Ni0.8O1.2/Al2O3 catalyst was performed using low-temperature nitrogen adsorption, powder X-ray diffraction, electron microscopy and thermal analysis. It was established that the mesoporous texture of the catalyst was retained, but the dispersion of the active component decreased. The Ce0.2Ni0.8O1.2/Al2O3 catalyst is resistant to thermal sintering and coking, which ensures no deactivation. The use of tri-reforming technology for the utilization of coal mine methane is a step towards “green” coal mining, ensuring sustainable development of society.